(untitled) (American Journal of Smart Technology and Solutions, 2025)
Adopting e-technology is a transformative approach to enhancing agricultural productivity, optimizing resource utilization, and improving market access in Bangladesh. However, its adoption remains low among farmers in flood-prone areas like Jamalpur due to inadequate digital infrastructure, limited digital literacy, and financial constraints. This study examines the factors influencing e-technology adoption in Charpara Block, Laxirchar Union, Jamalpur District, through structured interviews with 50 farmers. The findings indicate that only 30% of farmers use e-technology, primarily due to poor mobile network coverage, lack of awareness, and affordability issues. Farmers with larger landholdings, higher education levels, and organizational involvement demonstrated a greater likelihood of adoption. To address these barriers, this study proposes key policy interventions, including government-led subsidies for smartphones and internet services, expansion of digital literacy programs, and investment in rural network infrastructure to enhance accessibility. Additionally, technological solutions such as mobile-based advisory platforms (e.g., Krishoker Janala), AI-driven decision-support systems, and precision agriculture tools can improve climate resilience and optimize farm management. By integrating these measures, policymakers can bridge the digital divide and enhance agricultural sustainability. Addressing these barriers and implementing targeted interventions can drive widespread e-technology adoption, leading to socio-economic empowerment and improved climate adaptation for smallholder farmers.